MOBILE ZAKAT EMPOWERMENT IN ZAKAT COLLECTION - Rendy Pambajeng Syahputra; Achsania Hendratmi (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
The utilization of mobile zakat-based technology on smartphones has been developed through the Zakat Kita application by Nurul Hayat. This research is a case study method. The results of the study indicate that the utilization of mobile zakat is conducted by using Zakat Kita in the process of collecting ZIS funds is still not optimal. The renewal of the system from the application itself is in the development stage; the lack of the maximum application marketing process carried out also causes the collection process through the application is still not optimal. The results of the study also showed that although the collection results through applications showed an increase, the number of users of the application did not show a significant improvement. Utilization of our zakat application has met the empowerment indicators set by the Puskas BAZNAS by fulfilling social, cultural, economic, propaganda and environmental indexes.Keywords: Utilization, Zakat Mobile, Technology, Zakat